The Death of Cacique Politics - Magno, Alexander R. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The decomposition of the old conservative power blocs was hastened recently by the open break of Salvador Laurel from the Aquino camp.Without a voice in the Cabinet, distrusted by business leaders satisfied with the performance of the economy, abandoned by his followers for more promising alliances and repudiated by the middle-class groups, Laurel's political disposition became increasingly untenable.